2020
DOI: 10.3390/biology9110410
|View full text |Cite
|
Sign up to set email alerts
|

First De Novo Transcriptome of the Copepod Rhincalanus gigas from Antarctic Waters

Abstract: Antarctic waters are the largest almost untapped diversified resource of our planet. Molecular resources for Antarctic organisms are very limited and mostly represented by sequences used for species genotyping. In this study, we present the first transcriptome for the copepod Rhincalanus gigas, one of the predominant zooplankton species of Antarctic waters. This transcriptome represents also the first molecular resource for an eucalanoid copepod. The transcriptome is of high quality and completeness. The prese… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 49 publications
1
2
0
Order By: Relevance
“…We also found that 24.3% of the protein families among seven species have patterns of annotated transcripts similar to previously sequenced and here re-assembled C. finmarchicus (Tarrant et al, 2014), C. sinicus (Yang et al, 2014), and other recently investigated copepods, for example, Labidocera madurae (Roncalli et al, 2017) and Rhincalanus gigas (Lauritano et al, 2020).…”
Section: Conserved Protein Functions Across Speciessupporting
confidence: 83%
See 1 more Smart Citation
“…We also found that 24.3% of the protein families among seven species have patterns of annotated transcripts similar to previously sequenced and here re-assembled C. finmarchicus (Tarrant et al, 2014), C. sinicus (Yang et al, 2014), and other recently investigated copepods, for example, Labidocera madurae (Roncalli et al, 2017) and Rhincalanus gigas (Lauritano et al, 2020).…”
Section: Conserved Protein Functions Across Speciessupporting
confidence: 83%
“…finmarchicus (Tarrant et al, 2014 ), C . sinicus (Yang et al, 2014 ), and other recently investigated copepods, for example, Labidocera madurae (Roncalli et al, 2017 ) and Rhincalanus gigas (Lauritano et al, 2020 ).…”
Section: Discussionmentioning
confidence: 99%
“…Query sequences from the fruit fly Drosophila melanogaster (NP_524873, AAF07876, NP_572854) were used to mine the transcriptome shotgun assembly (TSA) database on the National Center for Biotechnology Information (NCBI), limiting the searches (tblastn algorithm) to Copepoda (taxid:6830) (search February 2023). For Rhincalanus gigas, raw reads were downloaded from NCBI [25] and assembled as described in [26]. Additional mining was performed using queries from the copepod Lepeophtheirus salmonis (order Siphonostomatoida) (BT121711, BT121232, MK887318, BT077723, BT121164) [14].…”
Section: In Silico Workflowmentioning
confidence: 99%